Konets Sankt-Peterburga . The End of St. Petersburg - Pudovkin, Vsevolod; Doller, Mikhail (Mosfilm, 1927)
Duration: 01:46:00 In a film designed to commemorate the 10th anniversary of the 1917 Bolshevik Revolution, Pudovkin again portrays the dawning of political awareness. The film stars Ivan Chuvelyov as a young peasant working a moribund farm. When his wife dies in childbirth in 1914, the young man heads for St. Petersburg, hoping to get help from his cousin (Aleksandr Chistykov), a factory worker. He's stunned by the pace of the city and awed by the mountainous buildings. His cousin is too preoccupied with the strike he's leading to be of any help to the lad, and the man's wife (Vera Baranovskaya) suggests he should return whence he came. The farmer unwittingly joins a group of strike breakers and naively tells the factory manager that the strikers he's curious about have been meeting at his cousin's house. Deaf to his attempts at atonement, his cousin's wife angrily tosses him into the street. Seeking revenge against the factory manager, the young man rolls through his office like a malefic tsunami before the police take him away. His education has begun.